Hubungan Faktor Sosial Ekonomi dengan Kejadian Pneumonia pada Anak Bawah Lima Tahun di Surakarta - Okti Rahmawati; Diffah Hanim; . Sumardiyono (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Background: Pneumonia is public health problem because of the high mortality rate, especially in infants and toddlers. This is caused by several factors, one of which is social and economic. Socio economic conditions will affect the health and disease patterns. This study aims to determine the relationship of socio economic factors to the incidence of pneumonia in children under five years (Toddlers) in Surakarta. Methods: This study was an observational study with cross-sectional design of which was held in March-April 2013 in the Balai Besar Kesehatan Paru Masyarakat (BBKPM). There were 60 subjects were taken by purposive-quota sampling method. The elderly subjects have been asked to fill out the form identity, written informed consent and questionnaires. Then the results of the questionnaire were tested with Chi Square through SPSS 17.0 for Windows. Results: The survey on respondents of maternal education were below the high school amounted to 38 respondens (63.33%) and 22 respondens (36.37%) above the high school. Occupational parents work, was privately held with non civil servant 57 people (95.00%) while a civil servant with 3 people (5.00%). As for the family income was below the minimum wage amounted to 32 people (53.33%) and above the minimum wage amounted to 28 people (46.67%). The analysis with Chi Square showed no association of maternal education (p = 0.072), family income (p = 0.194), and the work of parents (p = 0.350) with the incidence of pneumonia in infants. Conclusions: There was no relationship of socio economic factors (maternal education, parental employment and family income) with the incidence of pneumonia in young children in Surakarta. Keywords: Socio Economic, Toddler, Pneumonia